Fear of being left alone drives inefficient exit from partnerships: An experiment - Paolo Crosetto; Alexia Gaudeul; Gerhard Riener (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2014)
We explore in an experiment what leads to the breakdown of partnerships. Subjects are assigned a partner and participate in a repeated public good game with stochastic outcomes. They can choose each period between staying in the public project or working on their own. There is excessive exit as subjects overestimate the likelihood their partner will leave. High barriers to exit thus improve welfare. We observe that exit is driven by failure within the common project but also by pay-off comparisons across options and beliefs about being exploited. Those considerations increasingly matter as we lower exit costs across treatments.
Keywords: C23; C92; H41; 330; breakup; collaboration; cooperation; exit; imperfect public monitoring; moral hazard; partnerships; public good; punishment; repeated game; social risk; teams